A new tooth pitting modeling method based on matrix equation for evaluating time-varying mesh stiffness. (December 2022) - Meng, Fanshan; Xia, Heng; Zhang, Xin; Wang, Jiaxu
Highlights: A new tooth pitting modeling method based on matrix equation is proposed for evaluating mesh stiffness. Pits on the tooth surface follow probability distributions to model the propagation of the tooth pitting. The method can simulate the irregular shape pitting that better matches with the actual gear situation. The effectiveness of the method is demonstrated by comparing with the finite element results. Abstract: Tooth pitting is the most common gear failure, and it is usually modeled as regular shapes. Although this modeling approach simplifies the calculation, it is far from the real pitting shape. In this study, a new tooth pitting modeling method is proposed based on matrix equation. The method can generate irregular shape pitting and can customize the depth and shape accuracy of pits easily, making it more suitable for practical situations. Considering the pitting propagation, the pits are distributed statistically on gear tooth surface. Four pitting degrees and three pitting types are modeled by using this method, and then the stiffness of the pitting models are evaluated by potential energy method. The results show that the shapes and distribution forms of pitting have great influence on the time-varying mesh stiffness. The effectiveness of the stiffness evaluation is verified by comparing with the iSO-6336 and finite element results.